PEMODELAN MEDIA PENYARING UNTUK LIMBAH CHEMICHAL OXYGEN DEMAND (COD) DAN WARNA Studi Kasus Limbah dari Industri Batik Plentong Yogyakarta - , SEPTIAN VIENASTRA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Plentong Batik is one of the industries that developed among the batik industry in Yogyakarta. The industrial activity could produce wastewater that can make the around of environment being polluted. Concentration of waste can be reduced if the waste is passing through rock or sediment before being discharged into water bodies. The objectives of this study are (a) Comparing levels of Chemical Oxygen Demand (COD) and color from Batik Industry Plentong using modeling media filter with materials from the fluvio volcanic plain, alluvial and coastal plains during the week and (b) Spatial distribution mapping of pollutant load reduction of industrial waste (COD and color) batik using modeling media filter with sediment derived from volcanic plains feet, alluvial and coastal plains for a week. This research used sampling method. The data collected in this study a series filtering waste and without filtering for a week. There are three groups of material samples are used as filter media. The analysis methods are quantitative, descriptive, comparative and spatial analysis. The results of this study indicate that the value of decrease levels of COD and turbidity reduction of color used the first sample group (fluvio volcanic plain) has an average percentage are 16,06% and 13,18%